2013
DOI: 10.1177/1420326x13499361
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the air temperature of transitional spaces of a high-rise office building: The effects of season and location

Abstract: Recent increases in the awareness of sustainable green design have resulted in the creation of transitional spaces in high-rise buildings. Incorporating green design in high-rise buildings has been associated with the reduction of energy consumption in buildings and the provision of open spaces for occupants. Achieving thermal comfort in the outdoor environment is crucial, particularly in tropical climate settings where it is highly affected by microclimatic conditions such as the air temperature, wind, humidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Despite of the area size, the application of multi-layer planting on balcony must be fully considered in terms of the dimension and the climatic issue, especially if planted on a high-rise. The climatic condition on high-rise differs from the ground level due to the high amount of solar radiation and high wind velocity (Arslan & Sev, 2014;Taib, Abdullah, Ali, Fadzil, & Yeok, 2014). It is a buffer area and serves as a thermal bridge from the outdoor to the indoor and influenced by the various weather conditions from the outdoor.…”
Section: Site Selectionmentioning
confidence: 99%
“…Despite of the area size, the application of multi-layer planting on balcony must be fully considered in terms of the dimension and the climatic issue, especially if planted on a high-rise. The climatic condition on high-rise differs from the ground level due to the high amount of solar radiation and high wind velocity (Arslan & Sev, 2014;Taib, Abdullah, Ali, Fadzil, & Yeok, 2014). It is a buffer area and serves as a thermal bridge from the outdoor to the indoor and influenced by the various weather conditions from the outdoor.…”
Section: Site Selectionmentioning
confidence: 99%
“…It was concluded that different transmittance rates should be adopted for building canopy materials under different climatic conditions, and recommended values were given [17]. Other such articles have examined the relationship between microclimate and transition spaces [18][19][20], the effects of changes in wind speed due to fans [21], the rate of change of skin temperature on thermal comfort in transitional spaces [22], and so on [23,24]. However, a notable lacuna persists in terms of comprehensive multi-program comparisons and the judicious selection of appropriate scales to enhance the overall quality of the physical environment.…”
Section: Introductionmentioning
confidence: 99%
“…Cities today can be seen dotted with high-rise buildings, especially in the central business districts, to accommodate a higher number of people within a relatively smaller building footprint. High-rise buildings are a consequent reaction of economic prosperity and the need for high-density living [1,2]. They also serve as a statement of power and development, as their construction is fraught with challenges and requires detail planning and financial outlay [3].…”
Section: Introductionmentioning
confidence: 99%